Zakat Pertanian: Ketentuan dan Kadar Perhitungan: Penyuluhan Perhitungan Zakat kepada Petani Jagung di Desa Pongongaila - Supandi Rahman (Scimadly Publishing, 2022)
Areas where the majority of the population work as zakat instruments can be a solution to poverty alleviation. Reality in the field, especially in Pongongaila Village, Pulubala District, Gorontalo Regency, the public's understanding of zakat as a religious command (vertical) and a solution to poverty (horizontally) is inadequate. In the initial discussion with one of the people who live in Pongongaila Village who happens to be a lecturer, he revealed that the practice of agricultural zakat was almost missed from the daily activities of corn farmers. When the harvest comes, the most that farmers can enjoy as gratitude for the corn harvest is alms. Meanwhile, as we all know, almsgiving is different from zakat. If the amount of alms is not regulated, then zakat is regulated, even not only in terms of the amount, but also the time of payment, the minimum limit (nisab), and the allocation of zakat funds. Departing from this, this service agenda is directed to provide an understanding of agricultural zakat to people who work as corn farmers in Pongongaila Village, Pulubala District, Gorontalo Regency.